Neutralization of H− near vicinal metal surfaces - Obreshkov, Boyan; Thumm, Uwe (My University, 2006)
We calculate the neutralization probability of H− ions due to charge transfer in collisions with metal vicinal surfaces. We apply a statistical Thomas-Fermi model with gradient correction to the kinetic energy and a local density approximation for the exchange-correlation energy to compute the ground-state electronic structure of the surface. In comparison with calculations for flat surfaces, we find work-function changes, induced by the vicinal superstructure, in good agreement with published experimental and theoretical data. We evaluate the shift and width of the H− affinity level resonance for fixed positions of the ion near the surface. For incident anions with a kinetic energy of 1keV, the calculated ion-neutralization probabilities depend sensitively on the impact direction, point of closest approach of the trajectory, and the surface morphology. We find that the ion survival is more likely if the H− ions approach the step from above, as compared to ions that approach a step from below under otherwise identical scattering conditions. In particular, the electron loss after reflection at a terrace of a monoatomically stepped Al surface is predicted to be resonantly enhanced if the ion approaches a step from below.